2004
DOI: 10.1097/01.alc.0000122101.13164.21
|View full text |Cite
|
Sign up to set email alerts
|

Ionotropic Glutamate Receptor Antagonists Modulate Cue‐Induced Reinstatement of Ethanol‐Seeking Behavior

Abstract: These results show that glutamate antagonism suppresses ethanol-seeking behavior induced by ethanol-paired stimuli. Furthermore, the data suggest that ionotropic glutamate receptors may have differential roles in mediation of this behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 42 publications
8
87
0
2
Order By: Relevance
“…The ability of GYKI 52466 to reduce ethanol-seeking behavior seems to be in agreement with previous studies concerning cocaine- (Cornish and Kalivas, 2000) as well as ethanol-seeking behavior, using the nonspecific AMPA/kainate antagonist CNQX (Bäckstrom and Hyytiä, 2004). Thus, the findings of the present study provide additional support regarding the proposed involvement of this glutamate receptor subtype in drug craving and relapse.…”
Section: Discussionsupporting
confidence: 92%
“…The ability of GYKI 52466 to reduce ethanol-seeking behavior seems to be in agreement with previous studies concerning cocaine- (Cornish and Kalivas, 2000) as well as ethanol-seeking behavior, using the nonspecific AMPA/kainate antagonist CNQX (Bäckstrom and Hyytiä, 2004). Thus, the findings of the present study provide additional support regarding the proposed involvement of this glutamate receptor subtype in drug craving and relapse.…”
Section: Discussionsupporting
confidence: 92%
“…Systemic delivery of AMPAR antagonists inhibits cue-induced cocaine (Bäckström and Hyytiä, 2003) and ethanol (Bäckström and Hyytiä, 2004) seeking, as well as methamphetamine (Miyatake et al, 2005) and amphetamine (Mead and Stephens, 1999) CPP and the induction and expression of amphetamine behavioral sensitization (Karler et al, 1991). Evidence suggests that the efficacy of the systemic delivery of AMPA antagonists is enacted at least in part by glutamatergic neurotransmission in the accumbens, because systemic administration of the AMPAR antagonist 2,3-dihydroxy-6-nitro-7-sulfamoylbenzo[f]quinoxaline-2,3-dion (NBQX) inhibited cueinduced reinstatement of cocaine seeking and was accompanied by decreased activity in NAcore neurons (Zavala et al, 2008).…”
Section: Pharmacological Inhibition Of Drug Seekingmentioning
confidence: 99%
“…The integrity of the corticoaccumbens glutamate pathway is required for expressing many drug-induced changes in behavior, including the sensitization To whom correspondence should be addressed: Karen K. Szumlinski, Ph.D., Department of Psychology, University of California Santa Barbara, Santa Barbara, CA, USA 93106-9660.of a drug's psychomotor-activating effects [e.g., 28-37], the development of tolerance to a drug's psychomotor-inhibiting effects [e.g., 38,39], drug-conditioned place-preference [e.g., 36,38,40-43], the maintenance of drug self-administration [e.g., [44][45][46] and the reinstatement of drug-seeking [47][48][49][50][51][52][53][54][55][56]. Further, in vivo microdialysis studies have revealed pronounced effects of either acute or repeated drug-induced changes in NAC or PFC extracellular levels of glutamate by a number of drugs of abuse, including: cocaine [e.g., 31,35,37, 47,53,57,58], amphetamines [e.g., 20,59,60-62, but see 63], alcohol [38,39,64], nicotine [65][66][67][68] and opiates [69,70], implicating drug-induced changes in presynaptic aspects of corticoaccumbens glutamate transmission in mediating the changes in behavior produced by drugs of abuse.…”
Section: Introductionmentioning
confidence: 99%